On three types of civilisation in recentyvism - Wróbel, Jerzy (Folia Philosophica, 2004)
The author of the article describes the current state of advanced civilization, which is based on extreme technology, digital and analogue techniques. In his article, he points that such over-sophisticated civilization [panphronic] creates certain threats and danger, which were described as globalization. The author notices certain antidote to this situation - it is included in the ideas of ethics of simple-mindedness. This way he assimilates - in a way - the philosophy of recentivism in an attempt at explaining its peculiarities, its panphronicity.